Hybrid Governance in Child Welfare: Negotiating State and Faith-Based Policy Regimes in Indonesia - Muhammad Sahrul; Alfan Ramdoni; Joli Apriansyah (PT ARRUS Intelektual Indonesia, 2026)
This article examines how child welfare in Indonesia is governed through the interaction of state regulation and faith-based welfare provision. Focusing on Muhammadiyah, one of the country’s largest Islamic organizations, it argues that child welfare institutions are best understood as hybrid governance arrangements rather than as mere extensions of the state or purely charitable entities. The study uses a qualitative document-based case study drawing on Indonesian laws and regulations, Muhammadiyah’s child care guidelines, organizational rules, and institutional data. Guided by hybrid governance and institutional logics perspectives, the analysis identifies the intersection of state, religious, professional, and community-philanthropic rationalities in the organization of care. The findings show that national policy and Muhammadiyah’s internal framework converge in prioritizing family-based care and positioning residential care as a last resort. At the same time, Muhammadiyah translates public policy into its own Islamic organizational language while retaining internal authority, moral legitimacy, and philanthropic capacity. The main tension lies not in ideological conflict between religion and the state, but in the practical governance of transformation, especially professionalization, accountability, coordination, and the shift from institution-centered provision toward family support. The article contributes to debates on child welfare reform, faith-based organizations, and hybrid governance in the Global South.